Performance assessment of upflow anaerobic sludge blanket (UASB) reactor in treating sewage - Lim, Felicia Pei Shih, 1994-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2018